ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUM MAHASISWA AKUNTANSI DI UNIVERSITAS WIJAYA KUSUMA SURABAYA DALAM MEMILIH KARIR SEBAGAI AKUNTAN PUBLIK (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2006)
Career public accountant is a career that is viewed promising bright prospect because this profession gives intellectual challenges and priceless studying experience. Nevertheless, conducted is Canada and USA, found that there was a decreasing number of talented college students who want to be a public accountant. The purpose of the research is to identified whether there are differences between college who choose career as a public accountant and non public accountant, considered from intrinsic factors, income, job market consideration, college student perception about advantages and disadvantages of public accountant profession, personality and gender. This study also investigates which factors significantly influence accounting student in choosing career. This research is survey research. Sample of this research is accounting college student. Questionnaires are given to 100 respondents from universities in Surabaya . The number of returned questionnaires are 99 and the number of usable questionnaires are 99. Mann Whitney and Chi Square were used to compare responses of college student choice in career as public accountant and non public accountant. The result indicates accountant and non public accountant considered from consideration perception,personality,gender. (2) This result also indicates that many college students who choose profession have Intrisic and High Income. (3) This research also proves that there is no difference of interest between man and woman in choosing career as a public accountant.